Cytokine profiles associated with induction of the anticryptococcal cell-mediated immune response. - Murphy, J W (1993)
Previous studies with a murine model have shown that immunization with cryptococcal culture filtrate antigen (CneF) emulsified in complete Freund adjuvant (CFA) induces two populations of anticryptococcal reactive CD4+ T cells. One population (TDH cells) transfers anticryptococcal delayed-type hypersensitivity (DTH), and the other population (Tamp cells) amplifies the anticryptococcal DTH response of given to recipient mice at the time of immunization of the recipient. Treatment of mice with cyclosporin A (CsA) ablates the induction of Tamp cells but not TDH cells. The present study focused on assessing the cytokines produced by spleen cells taken from CsA-treated and control (solvent-treated) mice at days 1, 2, 4, and 6 after immunization. Supernatants from the spleen cells cultured in vitro for 24 or 48 h in medium alone or with CneF, concanavalin A, or phorbol 12-myristate 13-acetate plus calcium ionophore were assessed for the presence of interleukin-2 (IL-2), gamma interferon (IFN-gamma), IL-4, IL-5, and tumor necrosis factor. Spleen cells from CneF-CFA-treated mice produced IL-2 and IFN-gamma, but not IL-4 or IL-5, constitutively and in response to CneF, indicating that CneF-CFA induces a Th1 response. Tumor necrosis factor was not produced. Anticryptococcal TDH cells developed in spleens in which there were low levels of IFN-gamma and IL-2 (CsA-treated, immunized mice), whereas anticryptococcal Tamp cells along with TDH cells matured in spleens in which production of IFN-gamma and IL-2 was high (solvent-treated, immunized mice). The data also suggest that IL-2 and IFN-gamma produced by Tamp cells early after adoptive transfer are influential in the development of the amplified anticryptococcal DTH response that has been observed in Tamp cell-recipient mice.